Relationship between promotion effectiveness and promotion mix of DNA Asia ICT Sdn. Bhd. / Farino Santani Lian - Lian, Farino Santani (Faculty of Business and Management, 2009)
This research was conducted for the purposed on the relationship between promotion effectiveness and Promotion mix of DNA Asia ICT SDN BHD. The main objective of this research is to identify if there is a positive relationship between promotion mix that and the promotion effectiveness of DNA Asia ICT SDN BHD. The respondent of this study was the customer of DNA Asia ICT SDN BHD. The amount of questionnaire that has been distributed to the customer of DNA Asia ICT SDN BHD is 50 sets. The conclusion of this study was the outcome from the survey analysis and findings. Through the research, it shows that the promotion effectiveness and promotion mix variables such as advertising, personal selling, public relation and sales promotion has a positive relationship.